Ungdomars fiktionsvanor - Lundström, Stefan; Svensson, Anette ; 0000-0002-6665-3990 (Forskning om undervisning och lärande, 2017)
This article reports on a questionnaire study conducted among Swedish teenagers aged 17-18. The study aims to map out their use of fictional texts through various media forms in the two contexts school and recreational time. The study, which has a quantitative approach, focuses on mediation, gender, and study orientation, when exploring the media habits of Swedish teenagers. The results show that although the participants read fiction, they spend much more time using fictional texts in other media forms, such as computer games, TV-series, and films. Gender differences are visible in that men play computer games and women read literature to a greater extent. There are few prominent differences concerning the choice of educational programme. Instead, the results show that divergence should be considered on an individual level, and that large differences in media use can occur within the same school class. The results are discussed from a media ecological as well as a mediatization perspective, and in relation to an educational context.
Keywords: Litteraturdidaktik